Genderovanost porodu jako příklad antropologického zkoumání lidské reprodukce: přehled klíčových konceptů - Ema Hrešanová (AntropoWebzin)
In the past few years social scientists have extensively focused on the domain of human reproduction. This focus has provided many incentives for the development of related social theory. Building on these recent scholarly discussions, which emphasize the central role played by human reproduction in our social lives, this paper focuses on childbirth as one of the peak reproductive events and on its gender aspects. Predominantly building on the anthropology of reproduction and gender and related scholarship in the social sciences, the paper‘s aim is to provide a review of key ideas and concepts that make the „genderedness“ of childbirth visible. First, I explain what constitutes the gendered nature of childbirth and in what ways gender relations shape the birthing process. I build on Connell’s distinction of three main theoretical understandings of gender. Subsequently, I focus on the cultural aspects of childbirth and demonstrate its cultural construction with regard to gender. Next I highlight the importance of gender roles which are deeply internalized and work even during the birthing process, thus affecting the whole birthing experience. The interaction between medical personnel and a birthing woman is in itself an important part of this experience in Western societies and is shaped by the the overall medicalization of childbirth, which I then go on to discuss. Sunsequesntly, I focus on the issue of modern obstetrics as the ultimate source of authoritative knowledge. Childbirth however is also a crucial lifecycle event accompanied by rite de passage in non-Western as well as Western societies and the conclusion of this paper is therefore dedicated to presenting key works and ideas related to this important anthropological concept in relation to childbirth.